Polytechnic Education in the Distruption of Technology and Industrial Revolution 4:0 - Toyipur Toyipur (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
The learning system in the majority of Polytechnics uses Blended Learning systems including face to face, practice / workshop and online with learning composition; 40% theory and 60% practice with industry link and match mechanisms. For industry link and match, a comprehensive policy between ministries is needed to determine the functional position of the Learning Technology Developer (PTP) as an integrated manager of the learning program in tertiary institutions especially the Polytechnic both various learning resources, methods, teaching materials, media and learning environments so that learning outcomes can increase the production of goods and services quickly, effectively and efficiently through meaningful, enjoyable learning. The method used in this research is